Some problems related to the integration of members of the Islamic community in the Spanish Social Security System - Cervilla Garzón, María José (CUADERNOS DE DERECHO TRANSNACIONAL, 2023)
Two types of problems that may affect members of the Islamic community, regarding their posible integration into the Spanish Social Security System are addressed in this study. On the one hand, those derived from the posible provision of services, in the Islamic country of origin and in Spanish territory, being necessary to coordinate the legislation of both states for there cognition of benefits. On the other, those caused by certain practices and institutions of Islamic law, not recognized by our legal system, with particular reference to the Kafala and the continuity that the Supreme Court doctrine may have had on there cognition of a widow’spension to all beneficiaries, in case of polygamous marriage.
Keywords: Spanish Social Security System; islamic community